CELLULAR HETEROGENEITY IN THE PRODUCTION OF AN ANTI-HAPTEN ANTIBODY - Mäkelä, O. (The Rockefeller University Press, 1967)
Single lymph node cells from rats immunized with a conjugate of 3-iodo-4-hydroxy-5-nitrophenyl acetic acid chloride (NIP) and chicken globulin were tested against either NIP or NNP conjugated with bacteriophage. NNP is related to NIP but has a nitro group instead of iodine. The conjugated phages were still infective but easily inactivated by anti-hapten sera at a serum concentration of 10(–7). Phages carrying a related hapten were less sensitive to antibody than phages conjugated with the immunogenic hapten. When NIP-T2 and NNP-T4 conjugates were incubated in microdrops containing a single lymph node cell from an anti-NIP animal, strong inactivation of either or both phages occurred in some cases. For the reasons given in the text this inactivation was considered to be due to anti-NIP antibody produced by the cell in the microdrop. Inactivation of the two kinds of phages by the anti-NIP cells was highly nonrandom; some cells inactivated almost all of the 1700 or so NIP-T2 phages in the drop but left almost all NNP-T4 phages viable. Others had a very strong cross-reaction and inactivated equal proportions (up to 75%) of both phages. The remaining active cells exhibited an intermediate degree of cross-reaction. Control experiments indicated that there was a true cellular heterogeneity in the specificity of the anti-NIP produced by different cells. They suggested that the observed heterogeneity of specificities was limited to the structure of the hapten and was not influenced by the structure of the carrier. As all the cells studied were induced by a single hapten, the observed cellular heterogeneity was probably not caused by a heterogeneous antigen. It seems more likely that latent heterogeneity was present in the cells before they were stimulated by the NIP hapten.